Employer Branding and Organizational Commitment in A Company Specialized in Technological Solutions for Means of Payment in Miraflores – Lima - Olórtegui Alcalde Luis Miguel; Gasparrini Cañas Víctor Gerardo; Saldaña Narro Julio Brayan; Marcelo Quispe Luis Alberto; Astor Paredes Kelly (Communications of International Proceedings, 2024)
The study's main purpose was to determine the association between employer branding and organizational commitment in a company specializing in technological solutions for means of payment in Miraflores-Lima. The research was characterized by having a quantitative approach, being basic and with a non-experimental - transversal design and a correlational scope. We worked with a census sample of 85 employees of the company studied, to which two questionnaires were applied, the first to measure the employer branding variable with 28 items, and the second to measure the organizational commitment variable with 26 items. Both instruments reported high reliability, evidenced by Cronbach's coefficients of 0.967 and 0.925, respectively. The results showed a statistically significant association (r=0.690; p<0.001) between both variables, indicating a moderate-magnitude positive relationship. In conclusion, it is inferred that an adequate employer branding strategy is related to high levels of organizational commitment.
Keywords: Employer branding; Organizational commitment; Employees.